Neonates Effects and Tolerability of Treprostinil in Hypertension with Persistent Pulmonary - Jozefkowicz, Mariela; Haag, Dora Fabiana; Mazzucchelli, María Teresa; Salgado, Gladys; Fariña, Diana (American Journal of Perinatology, 2020)
Objective The aim of this study was to establish the effects of treprostinil in congenital diaphragmatic hernia (CDH) patients with persistent pulmonary hypertension (PHT) after 1 week of treatment. Drug effects were assessed by oxygenation index (OI), clinical end points, serial biochemical markers, and pre- and posttreatment echocardiogram. Treatment complications were also described.Study Design This is a quasi-experimental study of neonates with PHT admitted to the NICU within 48 hours showing persistent clinical instability, receiving mechanical ventilation with FiO2 > 60%, milrinone therapy, and inhaled nitric oxide. Clinical data were compared before and after treprostinil treatment.Results Seventeen neonates met the inclusion criteria. Median age was 17 days. Before treatment, median OI was 20 (IQR: 12–27). Suprasystemic PHT was estimated by echocardiogram in 8/17 patients; the rest were systemic. After 1 week of treatment, 15/17 patients were alive and median OI was 8 (IQR: 5–12, p = 0.0089). There were no statistically significant changes in laboratory data. Echocardiogram still showed suprasystemic PHT in 20% of patients. Adverse effects included hypotension, hematoma at the infusion site, and surgical persistent ductus arteriosus (PDA) closure in 4/17 patients. Fourteen patients were discharged. The median treatment time was 61 days.Conclusion Treprostinil was well tolerated with satisfactory clinical response. Further studies are required to identify early responder subgroups.
Keywords: newborns; pulmonary hypertension; treprostinil; congenital diaphragmatic hernia; prostacyclin